Highly Efficient Self‐Healing Multifunctional Dressing with Antibacterial Activity for Sutureless Wound Closure and Infected Wound Monitoring. Issue 3 (20th November 2021) - Tang, Ning; Zhang, Rongjun; Zheng, Youbin; Wang, Jing; Khatib, Muhammad; Jiang, Xue; Zhou, Cheng; Omar, Rawan; Saliba, Walaa; Wu, Weiwei; Yuan, Miaomiao; Cui, Daxiang; et al.
Abstract: Wound healing represents a major clinical and public healthcare problem that is frequently challenged by infection risks, detrimental consequences on the surrounding tissues, and difficulties to monitor the healing process. Here we report on a novel self‐healing, antibacterial, and multifunctional wound dressing for sutureless wound closure and real‐time monitoring of the healing parameters. The self‐healing elastomer contains cetyltrimethylammonium bromide (CTAB) and has high mechanical toughness (35 MJ m −3 ), biocompatibility, and outstanding antibacterial activity (bactericidal rate is ≈90% in 12 h), enabling the wound dressing to effectively inhibit bacterial growth and accelerate infected wound healing. In vivo tests based on full‐thickness skin incision model shows that the multifunctional wound dressing can help in contracting wound edges and facilitate wound closure and healing, as could be evidenced by notably dense and well‐organized collagen deposition. The test provides an evidence that the integrated sensor array within the multifunctional wound dressing can monitor temperature, pH, and glucose level of the wound area in real‐time, providing reliable and timely information of the condition of the wound. Ultimately, the reported multifunctional dressing would be of high value in managing the burden associated with wound healing via personalised monitoring and treatment approaches, digital and other people‐centred solutions for health care. Abstract : A novel self‐healing elastomer‐based multifunctional wound dressing (MFWD) with desirable mechanical robustness, biocompatibility, and antibacterial activity is developed for effective wound management. MFWD assists in contracting wound edges, based on the excellent self‐healing ability of the elastomer. The wound status can also be comprehensively monitored and reported with this MFWD.